2015
DOI: 10.1016/j.euroneuro.2015.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor SP4 phosphorylation is altered in the postmortem cerebellum of bipolar disorder and schizophrenia subjects

Abstract: Transcription factors play important roles in the control of neuronal function in physiological and pathological conditions. We previously reported reduced levels of transcription factor SP4 protein, but not transcript, in the cerebellum in bipolar disorder and associated with more severe negative symptoms in schizophrenia. We have recently reported phosphorylation of Sp4 at S770, which is regulated by membrane depolarization and NMDA receptor activity. The aim of this study was to investigate SP4 S770 phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 59 publications
2
8
0
Order By: Relevance
“…However, contrasting findings have been reported as regard to the role of miR-155, with some studies suggesting it to be part of a negative feedback loop which downregulates synthesis of inflammatory cytokines [43] and other reports suggesting a putative pro-inflammatory role [42]. SP4 , one of miR-155-3p targets showing statistical significance in our study, codifies for a zinc finger transcription factor highly expressed in neurons and previously suggested to be involved in BD and SCZ [44]. Interestingly, acute in vitro treatment with lithium was found to stabilize SP4 protein via a reduction of its phosphorilation at serine 770 in cultured rat cerebellar granule neurons [45] Accordingly, the authors showed a significantly reduced phosphorilated SP4 (pSP4)/SP4 ratio in peripheral blood mononuclear cells from first-episode psychosis patients treated with lithium ( n = 6) compared to patients treated with other drugs ( n = 8) [45].…”
Section: Discussionsupporting
confidence: 63%
“…However, contrasting findings have been reported as regard to the role of miR-155, with some studies suggesting it to be part of a negative feedback loop which downregulates synthesis of inflammatory cytokines [43] and other reports suggesting a putative pro-inflammatory role [42]. SP4 , one of miR-155-3p targets showing statistical significance in our study, codifies for a zinc finger transcription factor highly expressed in neurons and previously suggested to be involved in BD and SCZ [44]. Interestingly, acute in vitro treatment with lithium was found to stabilize SP4 protein via a reduction of its phosphorilation at serine 770 in cultured rat cerebellar granule neurons [45] Accordingly, the authors showed a significantly reduced phosphorilated SP4 (pSP4)/SP4 ratio in peripheral blood mononuclear cells from first-episode psychosis patients treated with lithium ( n = 6) compared to patients treated with other drugs ( n = 8) [45].…”
Section: Discussionsupporting
confidence: 63%
“…The activity of the transcription factor plays an essential role in neuronal function. Abnormal gene expression of transcription factors can affect the development and function of the nervous system and may lead to mental diseases, including BD (Pinacho et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The specificity protein‐4 (SP4), a neurodevelopmental transcription factor, has been associated with numerous psychiatric disorders with reduced expression observed in first‐episode schizophrenia patients (Fuste et al ). SP4 acts to ensure appropriate neuronal migration during development (Ramos et al ; Zhou et al ) and polymorphisms have been associated with SZ, BD and MDD (Pinacho et al , ; Zhou et al , ). Reducing Sp4 expression in mice results in several cognitive dysfunctions including diminished vigilance driven by lower hit rate in the 5C‐CPT and increased trials to acquire reward associations in a within‐session probabilistic learning task (Young et al ).…”
Section: Genetic Manipulations Of Neurodevelopmentmentioning
confidence: 99%